How we treat diarrhea in pediatric transplant patients: a brief review - Minniear, Timothy Dean; Vora, Surabhi (Frontiers in Pediatrics, 2023)
Diarrhea is a common problem faced by both hematopoietic and solid organ transplant recipients. The differential diagnosis is wide, ranging from infectious to non-infectious causes and from benign to emergent illness. Here we present two patients with diarrhea and discuss our approaches to the diagnostic evaluation and management of transplant recipients with diarrhea. We also include a review of the literature and discuss areas in need of further study.